Transmission of Grapevine Leafroll-associated Virus 3 (GLRaV-3): Acquisition, Inoculation and Retention by the Mealybugs Planococcus ficus and Pseudococcus longispinus (Hemiptera: Pseudococcidae) - Krüger, K.; Saccaggi, D.L.; van der Merwe, M.; Kasdorf, G.G.F. (South African Journal of Enology and Viticulture, 2016)
The vine mealybug, Planococcus ficus (Signoret), and the longtailed mealybug, Pseudococcus longispinus (Targioni Tozzetti), are vectors of grapevine leafroll-associated virus 3 (GRLaV-3), one of the most abundant viruses associated with grapevine leafroll disease. To elucidate the transmission biology in South Africa, acquisition access periods (AAPs), inoculation access periods (IAPs) and the retention of the virus in starving and feeding first- to second instar nymphs were determined. The rootstock hybrid LN33 served as virus source and grapevines (Vitis vinifera L., cv. Cabernet franc) served as recipient plants. An AAP of 15 min or an IAP of 15 min was sufficient for Pl. ficus to acquire or transmit GLRaV-3, respectively. Nymphs of Pl. ficus retained the virus for at least eight days when feeding on a non-virus host and grapevine, and for at least two days when starving, and were then capable of transmitting it successfully to healthy grapevine plants. Nymphs of Ps. longispinus transmitted the virus after an AAP of 30 min and an IAP of 1 h. They retained the virus for at least three days when feeding on virus-free vines or starving. The GLRaV-3 infection rates of plants with Pl. ficus as vector varied with AAPs. These were lower (20 to 60%) for AAPs of 12 h or less than for AAPs of 24 h or more (80 to 100%). The findings are of importance for understanding the transmission biology of mealybug vectors and devising management strategies for grapevine leafroll.